Juridical Review of Confiscated Goods of Corruption Crime (Study of Decision Number 40/Pid.Sus/TPK/2020/PN Mdn) - Panjaitan, Retimelani; Br Tarigan, Rani Theresia; Sitinjak, Helprida Marstella; Aritonang, Zico Ricardo (JURNAL MERCATORIA, 2025)
This study aims to examine the enforcement of criminal law and legal certainty in asset confiscation related to corruption cases, by focusing on Decision No. 40/Pid.Sus/TPK/2020/PN Mdn. The case concerns a private actor who manipulated the procurement process of waste-processing machines in Tanjungbalai City, causing state losses of more than IDR 1.5 billion. Using a normative juridical method and statutory-case approach, the research analyzes relevant legal norms, legislation, and jurisprudence. The data sources include primary legal materials (statutes and court decisions), secondary materials (journals and legal commentaries), and tertiary materials (legal dictionaries). The analysis shows the defendant violated Article 2(1) and Article 18 of Law No. 31/1999 in conjunction with Law No. 20/2001, supported by Article 55(1) of the Indonesian Penal Code. In addition to imprisonment, the court imposed a restitution penalty, enforceable through asset seizure and auction. The urgency of this issue lies in the challenge of recovering state losses when assets are in the name of third parties. This decision highlights the significance of legal certainty and enforceability in asset confiscation rulings, especially in corruption cases involving non-state actors. This research contributes to legal development in anti-corruption enforcement and provides a precedent for how asset recovery should be implemented.